Pengaruh Akuntabilitas Kinerja, Tipe Pemerintah Daerah, Temuan Audit, Dan Opini Auditor Terhadap Audit Delay Pada Pemerintah Kabupaten/Kota Di Indonesia - Putro, Dimas Hendrawan Mursito, Dra. Nursiam, M.H., Ak., CA (2017)
Delayed financial reports cause the reports loss their capacity in decision making. Audit delay is one of causative factors that influence towards the timeliness of financial report. This research was conducted to investigate influences of accountability performances, types of local government, audit findings, and auditors' opinions towards audit delay at local governments in Indonesia. This research used 234 local governments as research sample chosen by purposive sampling method. The research data were secondary data that was financial reports of regency/city government calculation year 2014 audited by State Audit Agency. The result of research concluded that accountability performances, audit findings, and auditors' opinions gave significant influence towards audit delay at regencies/cities governments in Indonesia. On the other hand, types of local government did not give significant result towards audit delay at regencies/cities government in Indonesia.